Detecting and managing hypertensive disorders in pregnancy: a cross-sectional analysis of the quality of antenatal care in Nigeria - Angela Salomon; Salisu Ishaku; Karen R. Kirk; Charlotte E. Warren (BMC Health Services Research, 2019)
Abstract Background Nigeria has one of the highest rates of maternal mortality in the world (576/100,000 births), with a significant proportion of death attributed to hypertensive disorders in pregnancy (HDPs). High quality antenatal care (ANC) plays a crucial role in early detection and management of HDPs. We conducted an assessment of quality of antenatal care, and its capacity to detect and manage HDPs, in two tiers of Nigerian facilities, with the aim of describing the state of service delivery and identifying the most urgent gaps. Methods Quality of antenatal care was assessed and compared between primary healthcare centers (PHCs) (n = 56) and hospitals (secondary + tertiary facilities, n = 39) in seven states of Nigeria. A cross-sectional design captured quality of care using facility inventory checklists, semi-structured interviews with healthcare providers and clients, and observations of ANC consultations. A quality of care framework and scoring system was established based on aspects of structure, process, and outcome. Average scores were compared using independent sample t-tests and measures of effect were assessed by multivariate linear regression. Results All domains of quality except provider interpersonal skills scored below 55%. The lowest overall scores were observed in provider knowledge (49.9%) and provider technical skill (47.7%). PHCs performed significantly worse than hospitals in all elements of quality except for provider interpersonal skills. Provider knowledge was significantly associated with their level of designation (i.e., obstetrician vs. other providers). Conclusions In order to provide high quality care, ANC in Nigeria must experience massive improvements to inventory, infrastructure and provider knowledge and training. In particular, ANC programs in PHCs must be revitalized to minimize the disparity in quality of care provided between PHCs and hospitals. The relatively low quality of care observed may be contributing to Nigeria’s high rate of maternal mortality and burden of disease attributed to HDPs.